Erratum: Macroeconomic Effects of Financial Shocks - Jermann, Urban; Quadrini, Vincenzo (American Economic Review, 2012)
Covas and den Haan (2011) find a procyclical pattern for debt issuance (consis tent with the countercyclicality of our debt repurchases) but the cyclical pattern for the 'aggregate' measure of equity issuance depends on the particular definition of equity issuance. When they use their preferred measure based on the change in the book value of equity (with or without subtracting dividends), they find a positive correlation with GDP. However, when they use the sales of stock net of share repur chases, they find a negative correlation with GDP (consistent with our procyclical equity payouts). See their Table 5.